The mediating role of psychological flexibility on the relationship between academic emotions, academic engagement, and academic achievement among university students - Ginesa López-Crespo; Goshgar Mursalzade; Noelia Sánchez-Pérez; Sonsoles Valdivia-Salas (Frontiers in Psychology, 2025)
Previous literature has proven the positive relationship of academic emotions, academic engagement and academic achievement. However, less is known about the impact of what students do in response to this emotions - that is, their psychological flexibility- on academic engagement and achievement. Therefore, the main purpose of the present study was to investigate the role of psychological flexibility in the relationship between academic emotions, engagement and achievement in a sample of university students. With this purpose, 261 psychology students, aged 18 to 26, participated in a cross-sectional survey study. The results of the study revealed a significant mediator role of psychological flexibility between the academic emotions of enjoyment and study academic achievement. Specifically, enjoyment was related to academic achievement both directly and indirectly through psychological flexibility. In contrast, study boredom did not have a direct relationship with academic achievement, but an indirect relationship mediated both by psychological flexibility and by the influence of psychological flexibility on engagement. These findings highlight the importance of psychological flexibility in the academic environment, showing its potential to help students to improve their academic performance regardless of the valence of the emotion experienced during their studies.